2017
DOI: 10.1007/s00268-017-4014-7
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Acute Surgical Patients at a District Hospital in Uganda with Non‐physician Emergency Clinicians

Abstract: Specialized non-physician clinicians practicing in a dedicated Emergency Department can perform resuscitation, bedside imaging and laboratory studies to aid in diagnosis of acute surgical patients and arrange transfer to an operating theater in an efficient fashion. This model has the potential to sustainably address structural and human resources problems inherent to Sub-Saharan Africa's current acute surgical care model and will benefit from further study and expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…[31][32][33] Several studies have shown that training nonphysician providers in emergency care services is both feasible and associated with improved outcomes in resource-limited settings. [32][33][34][35][36][37][38] At the present time, The Gambia does not have a prehospital Emergency Medical Service (EMS) and there are no trained physicians or mid-level providers in emergency medicine, even though it has been reported that more than one-half of all deaths and around one-third of all disability-adjusted life years in LMICs like The Gambia could be addressed through prehospital and facility-based EMS. 39 The transport time to a health facility was under one hour for most respondents.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Several studies have shown that training nonphysician providers in emergency care services is both feasible and associated with improved outcomes in resource-limited settings. [32][33][34][35][36][37][38] At the present time, The Gambia does not have a prehospital Emergency Medical Service (EMS) and there are no trained physicians or mid-level providers in emergency medicine, even though it has been reported that more than one-half of all deaths and around one-third of all disability-adjusted life years in LMICs like The Gambia could be addressed through prehospital and facility-based EMS. 39 The transport time to a health facility was under one hour for most respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The unit covers the ED, but does not provide critical care or trauma care. No comprehensive ACS model was in place in Rwanda and Uganda [69,70].…”
Section: Africamentioning
confidence: 99%
“…The important study by Wilhelm et al. adds to others 1 that this is not the case. Nonetheless, the notion may die hard.…”
mentioning
confidence: 93%